2010
DOI: 10.1007/s00482-010-0944-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronischer Rückenschmerz

Abstract: The study contributes to the methodological stability of two postulated groups. Thus further research should foster the development of risk-based interventions to evaluate if these groups offer an appropriate differentiation in rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Mostly as expected, patients with distress-avoidance responses (DAR) emerged as the patient group with the most severe levels of stress, maladaptive coping, and bad health. This is largely in line with meta-analytical data concerning the impact of activity avoidance on pain and (psychological) functioning as well as other cluster-analytical studies that also identified avoidance responders, mixed, or extreme cyclers as (one of) the most dysfunctional patient groups [15][16][17][18][19]23].…”
Section: Differences Between Pain Response Profiles In Secondary Meassupporting
confidence: 85%
See 3 more Smart Citations
“…Mostly as expected, patients with distress-avoidance responses (DAR) emerged as the patient group with the most severe levels of stress, maladaptive coping, and bad health. This is largely in line with meta-analytical data concerning the impact of activity avoidance on pain and (psychological) functioning as well as other cluster-analytical studies that also identified avoidance responders, mixed, or extreme cyclers as (one of) the most dysfunctional patient groups [15][16][17][18][19]23].…”
Section: Differences Between Pain Response Profiles In Secondary Meassupporting
confidence: 85%
“…Similar to clusters of depressive avoidance responders, mixed, or extreme cyclers, which were found in prior cluster-analytical studies [16][17][18][19], only one compound profile of mixed distress-avoidance responders (DAR) consistently emerged that showed both higher levels of fear-avoidance and medium levels of distress-endurance responses as compared to both other response profiles. Against our assumptions according to the FAM and AEM, we did not find a distinct profile of pure fear-avoidance responses.…”
Section: Plos Onesupporting
confidence: 62%
See 2 more Smart Citations